Autoeficacia y adherencia terapéutica en personas con diabetes mellitus tipo 2 - González-Cantero, Joel Omar (2015)
Diabetes mellitus 2 (DM2) is exacerbated when people do not adhere to their treatment. It requires evaluating the factors that influence favorably the achievement of adherence to treatment. Objective. Evaluate the relationship between self-efficacy and adherence to treatment in patients with DM2 served in Family Medicine Unit No. 48 (UMF 48) of the Instituto Mexicano del Seguro Social (IMSS). Method. Descriptive-correlational with 314 participants. Were applied the Scale of Adherence to the Treatment of Diabetes Mellitus Type II version III (EATDM - III) and the Spanish Diabetes Self-Efficacy. Results. Self-efficacy is positively and significantly associated with adherence to treatment (r = .400, p < 0.01). People self-efficient were 3.46 times more adherent to their treatment than those who were not self-efficient (RM = 3.46, p < .05). Discussion and conclusions. The findings of this research suggest that self-efficacy has a favorable impact on adherence to treatment in this study population. It is suggested to perform interventions to strengthen self-efficacy of individuals with respect to the treatment of the DM2.